Meningkatkan Hasil Belajar Matematika Materi Penjumlahan Pecahan Menggunakan Model Problem Based Learning Pada Siswa Kelas IV SDN Rumintin 1 Kabupaten Tapin - Aisyah, Aisyah; Sunarno, Sunarno (Jurnal Pendidikan, Sains Dan Teknologi, 2024)
The existence of classroom action research (PTK) in mathematics learning about adding fractions occurred because student learning outcomes were still low, so this research was carried out in 2 cycles. This research was carried out in the even semester of the 2023/2024 academic year in class IV at SDN Rumintin 1. The subjects in this research were 27 fourth grade students, consisting of 19 male students and 8 female students. The results of the research showed that there was an improvement in teacher activity so that in cycle I and cycle II student activity was at the "Very Good" category, then student activity in cycle I was at the "Active" category and increased to "Very Active" in cycle II, and the results students' learning in the cognitive domain obtained classical completeness of 62.96%, the affective domain obtained 74.04% completeness and the psychomotor domain obtained 66.67% completeness, then the learning outcomes of these three domains increased in cycle II to 100%. Based on the results of this research, it is concluded that using the Problem Based Learning model can improve teacher activities, increase student activity so that student learning outcomes are complete.